Construction Logistics Safety Measures - Mohamad Husny Hamid, Zuhra Junaida; Ratin, Nurul Fatimah (International Journal of Supply Chain Management, 2020)
Ã¢â‚¬â€ Construction logistics plays as one of the important enablers to support rapid development and economy in Malaysia. Heavy trucks used in construction logistics provide the ability to move more and bigger materials for development and manufacturing. However, it caused many problems, particularly in safety aspects, to the community. Hence, it is crucial to investigate more on the safety measures practised in construction logistics activities to adopt the right safety guideline. Three objectives were established. Firstly, to investigate current state of construction logistics in Malaysia. The second objective is to determine the safety measures practised for construction logistics activities by using five indicators from construction safety and health programs: rules and regulations, communications, accident investigation, training and evaluation. Lastly, the objective is to recommend suggestion to improve current situation of construction logistics activities that possessed danger to communities. With extensive data collection, this study has succeeded in stipulating evidence to show: (1) lack of sterner enforcement to combat wrongdoings in construction logistics activities, (2) lack of communication and information sharing among stakeholders, from the authorities, industry players to the communities and (3) insufficient training for employees, particularly drivers. This research has also contributed to future safety performances in logistics company by providing a guideline to measure safety performances